Varicella epidemiology in Latin America and the Caribbean - Maria L. Ávila-Agüero; Sandra Beltrán; José Brea del Castillo; María Esther Castillo Díaz; Luis Eduardo Chaparro; Carmen Deseda; Roberto Debbag; Carlos Espinal; Luiza Helena Falleiros-Arlant; Antonio José González Mata; Mercedes Macías Parra; Fabiano Marques-Rosa; et al. (Taylor & Francis Group, 2018)
Introduction: The Latin American Society of Pediatric Infectious Diseases (SLIPE), with the support of the Americas Health Foundation (AHF), has developed a position paper on varicella prevention in Latin America and Caribbean countries (LAC). This article summarizes the most relevant aspects of varicella in LAC, and emphasizes the need to include the varicella vaccine in the national immunization programs in the Region and evaluate its impact disease burden. Areas covered: A systematic review was conducted of the medical evidence published and presented at various regional medical conferences on the disease burden in LAC, the advances made by prevention programs, the available vaccines in the Region, and their immunogenicity, efficacy, effectiveness, and safety. The different national varicella-prevention vaccination programs were reviewed, as was available information regarding the impact of these programs on the epidemiology of varicella in those countries implementing a varicella vaccine strategy. Following that initial publication, an update was conducted, including data from additional countries in the Region. Expert commentary: Varicella is a vaccine-preventable infectious disease, considered a 'benign disease' because of lower complication rates when compared with measles, pertussis. The incorporation of a two-dose varicella vaccine in national immunization schedules in all countries throughout LAC would be of great benefit to the health of the children.